Submillisecond X‐ray photon correlation spectroscopy from a pixel array detector with fast dual gating and no readout dead‐time. (19th April 2016) - Zhang, Qingteng; Dufresne, Eric M.; Grybos, Pawel; Kmon, Piotr; Maj, Piotr; Narayanan, Suresh; Deptuch, Grzegorz W.; Szczygiel, Robert; Sandy, Alec
Abstract : X‐ray photon correlation spectroscopy is performed using a dual counter pixel array detector at a frame rate of 11.8 kHz with no readout dead‐time. Abstract : Small‐angle scattering X‐ray photon correlation spectroscopy (XPCS) studies were performed using a novel photon‐counting pixel array detector with dual counters for each pixel. Each counter can be read out independently from the other to ensure there is no readout dead‐time between the neighboring frames. A maximum frame rate of 11.8 kHz was achieved. Results on test samples show good agreement with simple diffusion. The potential of extending the time resolution of XPCS beyond the limit set by the detector frame rate using dual counters is also discussed.